A non-precious metal-based catalyst modified with non-metallic elements in the p-zone and its preparation method and application
By introducing p-zone non-metallic elements into the MOF structure, the supported vM-wX/C catalyst was prepared, and the problem of tight supply and demand for noble metal catalysts was solved, and the acetylene conversion rate and ethylene selectivity in the acetylene selective hydrogenation reaction was improved, and good stability and efficient catalytic performance were shown.
Patent Information
- Application Number
- CN202310539003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-05-12
AI Technical Summary
Although existing precious metal Pd nanocatalysts have excellent H2 activation capabilities in acetylene selective hydrogenation reaction, the supply and demand gap has expanded due to the decrease in precious metal reserves and rising costs. It is necessary to develop resource-rich and low-cost non-precious metal catalysts to replace precious metals.
By using the non-metallic elements of the p-region and the non-metallic element of the p-region, the M-X-MOF precursor is prepared by introducing the non-precious metal M and the non-metallic element of the p-region into the MOF structural unit, the M-X-MOF precursor is obtained through topological transformation, and the M-X bond and p-d hybridization are generated in the MOF structure using the non-metallic atoms of the p-region to form Mδ+-X active sites that are isolated on the surface and electrons are deleted.
The combined improvement of acetylene conversion rate and ethylene selectivity is achieved. The catalyst exhibits excellent stability and efficient catalytic performance, and the process is simple and there is no need to add surfactant.
Smart Images

Figure HDA0004233775140000011 
Figure HDA0004233775140000012 
Figure HDA0004233775140000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petrochemical industry and fine chemical industry, and specifically relates to a non-noble metal-based catalyst modified by a non-metallic element in a p-region, and a preparation method and application thereof. Background Art
[0002] Selective hydrogenation of trace acetylene impurities in ethylene raw materials is an important reaction in the petrochemical process, and its development level has a vital impact on the national economy. With the increasing demand for green chemical processes, higher requirements are placed on the production technology of polymer-grade ethylene and the acetylene content (<1ppm) in ethylene raw materials. 2 The activation ability can transform the reactants under mild reaction conditions, and thus it is widely used in the selective hydrogenation of acetylene. However, in recent years, the global reserves of precious metals have decreased sharply, and the prices have continued to rise, resulting in a widening gap between supply and demand. Therefore, the development of resource-rich and low-cost non-precious metal catalysts and the effective replacement of precious metals are of great significance to the sustainable development of green chemical processes.
[0003] Ni-based catalysts have a certain ability to activate hydrogen due to their unfilled d-electron orbitals, which has attracted widespread attention in the field of catalysis. 2 -supported Ni-Gaalloy and intermetallic compound.J.Energy Chem.2019,29,40-49 found that although the single metal Ni-based catalyst has a high ability to activate hydrogen, the continuous Ni sites are prone to over-hydrogenation and oligomerization reactions, resulting in poor ethylene selectivity. To address this problem, researchers often adjust the geometry and electronic structure of the single metal Ni by adding a second component to optimize the adsorption mode of the product / intermediate, thereby improving ethylene selectivity. Li et al. introduced Ag into the Ni system and loaded it on Al in Selective Hydrogenation of Acetylene to Ethylene over Bimetallic Catalysts.Ind.Eng.Chem.Res.2019,58,20620-20629. 2 O 3 On the support, bimetallic NiAg / Al 2 O 3 Catalyst. Compared with single metal Ni / Al 2 O 3 , NiAg / Al 2 O 3The catalyst exhibits higher selectivity, but at the expense of conversion rate. Since it is difficult to accurately control the distribution of bimetallic atoms in bimetallic catalysts prepared by traditional methods, it is easy to over-cover the active metal sites. Compared with transition metal elements, p-zone non-metallic atoms with smaller atomic size can enter the metal lattice gaps and carrier pores, and modify their microscopic geometry and electronic structure by inducing lattice distortion and pd orbital hybridization, thereby improving catalytic performance. Chan et al. used p-zone non-metallic B atoms to modify the gaps of Pd nanoparticles in Interstitial Modification of Palladium Nanoparticles with Boron Atoms as A Green Catalyst for Selective Hydrogenation. Nat. Commun, 2014, 5, 5787 to obtain Pd- int The B / C catalyst exhibits excellent catalytic activity and selectivity in the hydrogenation of alkynes. Density functional theory calculations show that the hybridization of the p orbital of B and the d orbital of Pd weakens the adsorption of reactants and intermediates on the catalyst surface.
[0004] Compared with other p-block non-metallic elements, S element has attracted widespread attention due to its advantages such as large atomic radius and electronegativity. The organic ligand modification strategy is usually used to introduce S element, but this method is prone to poisoning and covering of active sites. Metal-organic framework materials (MOF) are a class of porous polymers with periodic network structures formed by metal ions and organic ligands coordinated by covalent bonds or van der Waals forces. Due to the controllability of the composition, transition metals and non-metals with hydrogenation activity can be introduced into its metal nodes and organic ligands at a certain ratio, thereby showing excellent performance in a series of catalytic reactions. In addition, at a certain temperature, MOF materials can also undergo topological transformation to produce carbon materials with good thermal and chemical stability, providing an innovative platform for the preparation of industrial supported catalysts.
[0005] Based on this, the present invention utilizes the p-region non-metallic elements and MOF structural characteristics, introduces non-precious metal M with hydrogenation activity and p-region non-metallic element X that can serve as a structural additive into the MOF structural unit to prepare the MX-MOF precursor, and obtains the supported vM-wX / C catalyst by regulating the topological transition temperature. The introduced p-region non-metallic atoms enter the octahedral gap of the transition metal M during the MOF structural topological process, spatially separate the continuous M sites, and generate pd orbital hybridization with them, thus constructing a surface-isolated and electron-deficient M δ+-X active sites, thereby achieving a joint improvement in acetylene conversion and ethylene selectivity. In addition, some p-region non-metal atoms X bonded with the C support to form unsaturated coordinated nucleation centers, which enhanced its interaction with the active components, inhibited the migration and agglomeration of M during the reaction, and made the catalyst show excellent stability. Summary of the invention
[0006] The purpose of the present invention is to provide a non-noble metal-based catalyst modified with a non-metallic element in a p-zone, and a preparation method and application thereof.
[0007] The catalyst provided by the present invention is expressed as vM-wX / C, wherein M represents a transition metal with hydrogenation activity; the M is one or two of Ni, Co, Cu, Fe and Zn, preferably one or two of Ni or Cu; v represents the loading amount of the transition metal M, v=5.0-20.0wt.%, preferably 5.0-10.0wt.%; X is one or two of p-zone non-metallic elements P, S, N and B, preferably one or two of S, P or B; w represents the loading amount of X, w=0.5-2.0wt.%, preferably 1.0-2.0wt.%.
[0008] The structural characteristics of the above catalyst are: the active component particles are uniformly dispersed on the C carrier doped with non-metallic X in the p-region, and the non-metallic X in the p-region occupies the octahedral gap of the transition metal M particles to produce MX bonds. Through the regulation of the distance between M atoms and the pd hybridization between M atoms and X, M with discontinuous surface atoms and missing electrons is formed. δ+ -X site.
[0009] The present invention provides a method for preparing a non-precious metal-based catalyst modified with a p-zone non-metallic element, and the specific steps are as follows:
[0010] A. Dissolve the soluble transition metal salt and the organic ligand in excess N,N-dimethylformamide at a molar ratio of 1 to 2 / 1 to prepare a solution with a transition metal concentration of 70.0 to 110.0 mmol / L. Transfer the solution to a reactor, crystallize at 120 to 150°C for 12 to 20 hours, cool naturally to room temperature, centrifuge, wash, and place in a 60 to 90°C constant temperature drying oven for 12 to 24 hours to obtain a transition metal-based organic metal framework material M-MOF;
[0011] The soluble transition metal salt is Ni(NO 3 ) 2 6H 2 O、NiCl 2 、Co(NO 3 ) 2 6H 2 O, Cu(NO 3) 2 ·3H 2 O、Zn(NO 3 ) 2 6H 2 O, FeCl 2 ·4H 2 O, wherein M is one or two of the corresponding transition metals Ni, Co, Cu, Fe, Zn; the organic ligand is one of terephthalic acid, phthalic acid, 2,2-bipyridine or 2,5-dihydroxyterephthalic acid;
[0012] B. dissolving an organic compound containing a p-region non-metal X in excess anhydrous methanol to prepare a solution with a concentration of 2 to 6 mol / L, and mixing it with the M-MOF precursor prepared in step A at an X / M molar ratio of 1 / 5 to 1 / 15, stirring continuously at a constant temperature of 25 to 60° C. for 10 to 20 hours, centrifugally filtering and washing, and drying in a constant temperature drying oven at 60 to 90° C. for 12 to 24 hours to obtain a transition metal-based organic metal framework material modified with a p-region non-metal X, denoted as MX-MOF;
[0013] The organic compound containing the p-block non-metal X is one or two of dimethyl sulfoxide, thiourea, dicyandiamide, triphenylphosphine, sodium hypophosphite or boric acid;
[0014] C. The MX-MOF obtained in step B is placed in a fixed bed reactor, and the temperature is raised to 200-600°C at a rate of 2-20°C / min in an inert atmosphere, and maintained for 1-3 hours to induce a structural topological transformation of the MOF precursor. After cooling to room temperature, a highly dispersed M-MOF with non-metallic X modification in the p region is obtained. 2+ -X / C precursor;
[0015] The inert atmosphere is N 2 , Ar or He;
[0016] D. placing the sample obtained in step C in a micro fixed bed reactor, introducing a reducing atmosphere, heating the temperature to 200-500° C. at a heating rate of 2-20° C. / min, and maintaining the temperature for 1-3 hours for activation, and cooling the temperature to room temperature to obtain a carbon-supported non-precious metal-based catalyst modified with a p-region non-metallic element, expressed as vM-wX / C; M represents an active metal, X represents a p-region non-metallic element, v represents the loading amount of the transition metal M, and w represents the loading amount of the p-region non-metallic element X;
[0017] The reducing atmosphere is 5-40 vol.% H 2 / N 2 or 5~40vol.%CO / N 2 One of them.
[0018] Figure 1 This is the X-ray diffraction (XRD) spectrum of 10% Ni-1% S / C prepared in Example 1. As can be seen from the figure, compared with the 10% Ni / C reference sample, the characteristic peak of the 10% Ni-1% S / C catalyst prepared in Example 1 shifts to a high wave number by 0.11°, indicating that S atoms are inserted into the Ni lattice and occupy interstitial or substitution sites.
[0019] Figure 2 This is a high resolution transmission electron microscope (HRTEM) photo of the 10% Ni-1% S / C catalyst prepared in Example 1. It can be seen from the HRTEM photo that the 10% Ni-1% S / C catalyst particles prepared in Example 1 are uniformly dispersed and the lattice fringes are 0.205nm, which is larger than the lattice spacing of metal Ni (0.203nm), indicating that S atoms occupy the lattice gaps of Ni atoms, causing the lattice gaps to expand.
[0020] Figure 3 X-ray photoelectron spectroscopy (XPS) spectra of 10% Ni-1% S / C and 10% Ni / C reference samples prepared in Example 1. It can be seen from the spectra that compared with the 10% Ni / C reference sample, the Ni metal characteristic peak in the 10% Ni-1% S / C catalyst moves to high energy, indicating that Ni is in an electron-deficient state.
[0021] Figure 4 This is the Fourier transform X-ray absorption fine structure (EXAFS) spectrum of Ni K edge of the 10% Ni-1% S / C catalyst prepared in Example 1. From the figure, the Ni-S coordination characteristic peaks and Ni-Ni coordination characteristic peaks of the 10% Ni-1% S / C catalyst can be observed, indicating that the introduction of S element forms Ni-S coordination with Ni atoms.
[0022] Figure 5 The TOF of 10% Ni-1% S / C and 10% Ni / C reference samples prepared in Example 1 is shown in the figure. It can be seen from the figure that the TOF value of 10% Ni-1% S / C catalyst is about three times that of 10% Ni / C, indicating that the intrinsic activity of 10% Ni-1% S / C is enhanced.
[0023] Figure 6 The experimental results of the 10% Ni-1% S / C catalyst prepared in Example 1 in the selective hydrogenation reaction of acetylene, a is the curve of acetylene conversion and temperature, b is the curve of ethylene selectivity and temperature. When the reaction temperature is 178°C, the acetylene conversion is 100% and the ethylene selectivity is 92%.
[0024] Figure 7This is the stability curve of the 10% Ni-1% S / C catalyst prepared in Example 1 in the selective hydrogenation reaction of acetylene. It can be seen that the catalyst reacted continuously at 165°C for 12 hours, with points taken every 30 minutes. The acetylene conversion rate only showed a slight decrease, and the ethylene selectivity remained at 90±2%, indicating that the catalyst has good long-term stability.
[0025] Beneficial effects of the present invention:
[0026] The preparation method provided by the present invention is characterized in that: utilizing the tunability of MOF composition, a post-modification doping method is used to introduce p-region non-metallic elements into the M-MOF precursor, and through topological transformation, p-region non-metallic atoms are induced to enter the active metal octahedral gap and the carrier surface, and the active components and the carrier geometry and electronic structure are modified to obtain a highly dispersed supported vM-wX / C catalyst. The preparation conditions are mild, no surfactant needs to be added during the preparation process, and the process is simple.
[0027] The structural characteristics of the prepared supported vM-wX / C catalyst are as follows: the p-region non-metallic elements occupy the gaps between the surface active metal octahedra through the structural topological effect, achieving effective spatial isolation of the continuous active M sites, and reducing the degree of electron filling of the active metal M through the pd hybridization of X and M. At the same time, the introduced p-region non-metallic X forms a CX bond with the carrier to anchor the active metal particles, which makes the catalyst have good structural stability and solves the problem that the distribution of multi-metal atoms in the supported catalyst prepared by the traditional impregnation method is difficult to control and the active sites are easily covered, resulting in poor catalytic performance.
[0028] The catalyst is used in the selective hydrogenation reaction process of acetylene, has excellent acetylene hydrogenation activity and ethylene selectivity, outstanding catalytic performance, is easy to recover and reuse, and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The XRD spectra of the 10% Ni-1% S / C catalyst and the 10% Ni / C reference sample prepared in Example 1. a is the XRD spectra of the 10% Ni-1% S / C catalyst and the 10% Ni / C reference sample prepared in Example 1, and b is a partial enlarged view.
[0030] Figure 2 HRTEM images of the 10% Ni-1% S / C catalyst prepared in step D of Example 1. a is a local HRTEM image of the 10% Ni-1% S / C catalyst prepared in step D of Example 1, and b is a lattice fringe image of the 10% Ni-1% S / C catalyst prepared in step D of Example 1.
[0031] Figure 3X-ray photoelectron spectroscopy (XPS) of Ni 2p orbitals of the 10% Ni-1% S / C catalyst prepared in step D of Example 1 and the 10% Ni / C reference sample.
[0032] Figure 4 This is the Ni K-edge EXAFS spectrum of the 10% Ni-1% S / C catalyst prepared in Step D of Example 1.
[0033] Figure 5 Figure 2 is the turnover frequency (TOF) of the 10% Ni-1% S / C catalyst prepared in step D of Example 1 and the 10% Ni / C reference sample at low conversion rate. a is the TOF bar graph of the 10% Ni-1% S / C catalyst prepared in Example 1, and b is the TOF bar graph of the 10% Ni / C reference sample.
[0034] Figure 6 These are the experimental results of the 10% Ni-1% S / C catalyst prepared in step D of Example 1 in the selective hydrogenation reaction of acetylene. a is the curve of acetylene conversion versus reaction temperature, and b is the curve of ethylene selectivity versus acetylene conversion.
[0035] Figure 7 This is the stability curve of the 10% Ni-1% S / C catalyst prepared in Example 1 in the selective hydrogenation reaction of acetylene. DETAILED DESCRIPTION
[0036] Example 1
[0037] A. Put Ni(NO 3 ) 2 6H 2 O and terephthalic acid were dissolved in excess N,N-dimethylformamide at a molar ratio of 1 / 1, and ultrasonicated until completely dissolved to prepare a solution with a transition metal concentration of 83.1mmol / L. The solution was transferred to a reactor, crystallized at 120°C for 15h, cooled naturally to room temperature, centrifuged, washed, and placed in a 60°C constant temperature drying oven for 24h to obtain a transition metal-based organic metal framework material Ni-MOF;
[0038] B. Dissolve dimethyl sulfoxide containing p-region non-metallic atom S in excess anhydrous methanol to prepare a solution with a concentration of 2.8 mol / L, and mix it with the Ni-MOF precursor prepared in step A at a S / Ni molar ratio of 1 / 10, stir it continuously at a constant temperature of 25°C for 12 hours, centrifuge and wash it, and dry it in a constant temperature drying oven at 60°C for 24 hours to obtain a transition metal-based organic metal framework material modified with p-region non-metallic atom S, which is represented by Ni-S-MOF;
[0039] C. The Ni-S-MOF obtained in step B is placed in a fixed bed reactor under N2 The temperature was raised to 300 °C at a rate of 10 °C / min in the atmosphere and maintained for 1 h to induce the structural topological transformation of the MOF precursor. After cooling to room temperature, a highly dispersed Ni-S-modified p-region was obtained. 2+ -S / C precursor;
[0040] D. Place the sample obtained in step C in a fixed bed reactor and introduce 10 vol.% H 2 / N 2 Reducing atmosphere, heating to 300°C at a heating rate of 10°C / min, and maintaining for 2h, and then cooling to room temperature to obtain a p-zone non-metallic S element-modified carbon-supported Ni-based catalyst, expressed as 10% Ni-1% S / C;
[0041] Example 2
[0042] A.Cu(NO 3 ) 2 ·3H 2 O and 2,5-dihydroxyterephthalic acid were dissolved in excess N,N-dimethylformamide at a molar ratio of 1 / 1.5 to prepare a solution with a transition metal concentration of 100.0mmol / L. The solution was transferred to a reactor, crystallized at 150°C for 15h, cooled naturally to room temperature, centrifuged, washed, and placed in a 60°C constant temperature drying oven for 24h to obtain a transition metal-based organic metal framework material Cu-MOF;
[0043] B. Dissolve dimethyl sulfoxide containing p-region non-metallic atom S in excess anhydrous methanol to prepare a solution with a concentration of 2.8 mol / L, and mix it with the Cu-MOF precursor prepared in step A at a S / Cu molar ratio of 1 / 10, stir it continuously at a constant temperature of 25°C for 12 hours, centrifuge and wash it, and dry it in a constant temperature drying oven at 60°C for 24 hours to obtain a transition metal-based organic metal framework material modified with p-region non-metallic atom S, which is represented by Cu-S-MOF;
[0044] C. The Cu-S-MOF obtained in step B is placed in a fixed bed reactor under N 2 The temperature was raised to 500°C at a rate of 10°C / min in the atmosphere and maintained for 1 h to induce the structural topological transformation of the MOF precursor. After cooling to room temperature, a highly dispersed Cu2+-modified non-metallic S in the p-region was obtained. 2+ -S / C precursor;
[0045] D. Place the sample obtained in step C in a micro fixed bed reactor and introduce 10 vol.% H 2 / N 2In a reducing atmosphere, the temperature was raised to 500°C at a heating rate of 10°C / min and maintained for 2h. After cooling to room temperature, a p-zone non-metallic S element-modified carbon-supported Cu-based catalyst was obtained, expressed as 8% Cu-1% S / C.
[0046] Example 3
[0047] A. Put Ni(NO 3 ) 2 6H 2 O and terephthalic acid were dissolved in excess N,N-dimethylformamide at a molar ratio of 1 / 1 to prepare a solution with a transition metal concentration of 83.1mmol / L. The solution was transferred to a reactor, crystallized at 150°C for 20h, cooled naturally to room temperature, centrifuged, washed, and placed in a 60°C constant temperature drying oven for 24h to obtain a transition metal-based organic metal framework material Ni-MOF;
[0048] B. dissolving the boric acid containing the p-region non-metallic atom B in excess anhydrous methanol to prepare a solution with a concentration of 5.6 mol / L, and mixing it with the Ni-MOF precursor prepared in step A at a B / Ni molar ratio of 1 / 10, stirring continuously at a constant temperature of 60° C. for 12 h, centrifugally filtering and washing, and drying in a constant temperature drying oven at 60° C. for 24 h to obtain a transition metal-based organic metal framework material modified with the p-region non-metallic atom B, denoted as Ni-B-MOF;
[0049] C. The Ni-B-MOF obtained in step B is placed in a fixed bed reactor under N 2 The temperature was raised to 300 °C at a rate of 10 °C / min in the atmosphere and maintained for 1 h to induce the structural topological transformation of the MOF precursor. After cooling to room temperature, a highly dispersed Ni 2+ -B / C precursor;
[0050] D. Place the sample obtained in step C in a micro fixed bed reactor and introduce 10 vol.% CO / N 2 In a reducing atmosphere, the temperature was raised to 300°C at a heating rate of 10°C / min and maintained for 3h. After cooling to room temperature, a carbon-supported Ni-based catalyst modified with a non-metallic B element in the p-zone was obtained, which was expressed as 10% Ni-2% B / C.
[0051] Example 4
[0052] A.Cu(NO 3 ) 2 6H 2O and terephthalic acid were dissolved in excess N,N-dimethylformamide at a molar ratio of 1 / 1 to prepare a solution with a transition metal concentration of 110.0 mmol / L. The solution was transferred to a reactor, crystallized at 120°C for 15 hours, cooled naturally to room temperature, centrifuged, washed, and placed in a 60°C constant temperature drying oven for 24 hours to obtain a transition metal-based organic metal framework material Cu-MOF;
[0053] B. Sodium hypophosphite containing p-region non-metallic atom P is dissolved in excess anhydrous methanol to prepare a solution with a concentration of 2.8 mol / L, and mixed with the Cu-MOF precursor prepared in step A at a P / Cu molar ratio of 1 / 10, and stirred continuously at a constant temperature of 25° C. for 12 h, centrifuged and filtered, washed, and dried in a constant temperature drying oven at 60° C. for 24 h to obtain a transition metal-based organic metal framework material modified with p-region non-metallic atom P, represented by Cu-P-MOF;
[0054] C. The Cu-P-MOF obtained in step B is placed in a fixed bed reactor under N 2 The temperature was raised to 400°C at a rate of 10°C / min in the atmosphere and maintained for 1 h to induce the structural topological transformation of the MOF precursor. After cooling to room temperature, a highly dispersed Cu2+-modified non-metallic P in the p-region was obtained. 2+ -P / C precursor;
[0055] D. Place the sample obtained in step C in a micro fixed bed reactor and introduce 10 vol.% H 2 / N 2 In a reducing atmosphere, the temperature was raised to 400°C at a heating rate of 10°C / min and maintained for 3h. After cooling to room temperature, a carbon-supported Cu-based catalyst modified with a p-zone non-metallic P element was obtained, which was expressed as 10% Cu-1% P / C.
[0056] Example 5
[0057] A is the same as in Example 1;
[0058] B. Sodium hypophosphite and dimethyl sulfoxide containing p-region non-metallic atoms P and S are dissolved in excess anhydrous methanol to form a solution with a concentration of 2.8 mol / L, and mixed with the Ni-MOF precursor prepared in step A at a P / Ni and S / Ni molar ratio of 1 / 10, and stirred continuously at a constant temperature of 25°C for 12 hours, centrifuged and washed, and dried in a constant temperature drying oven at 60°C for 24 hours to obtain a transition metal-based organic metal framework material modified with p-region non-metallic atoms P and S, represented as Ni-PS-MOF;
[0059] C. The Ni-PS-MOF obtained in step B is placed in a fixed bed reactor under N 2The temperature was raised to 500°C at a rate of 10°C / min in an atmosphere and maintained for 1 h to induce a structural topological transformation of the MOF precursor. After cooling to room temperature, a highly dispersed Ni 2+ -PS / C precursor;
[0060] D. Place the sample obtained in step C in a fixed bed reactor and introduce 10 vol.% H 2 / N 2 In a reducing atmosphere, the temperature was raised to 500°C at a heating rate of 10°C / min and maintained for 3h. After cooling to room temperature, a carbon-supported Ni-based catalyst modified with p-zone non-metallic P and S elements was obtained, which was expressed as 10% Ni-1% P-1% S / C.
[0061] The catalysts prepared in the above-mentioned Examples 1 to 5 were used in the acetylene selective hydrogenation reaction experiment. The specific method was as follows: 0.1 g of the catalyst was weighed and mixed with 1.4 g of quartz sand with a particle size of 40 to 70 meshes, and then loaded into a quartz reaction tube with a diameter of 7 mm. The catalytic activity increased with the increase of the loading amount of the catalyst. In order to better compare the catalytic performance, the loading amount of the catalyst was controlled to be consistent. The gas composition in the reaction raw gas was 0.45 vol.% acetylene / 0.91 vol.% hydrogen / 45.00 vol.% ethylene / nitrogen balance gas. The catalytic performance test temperature was 70 to 190°C, the test temperature interval was 10°C, the test pressure was normal pressure, and the air velocity was 13200 h -1 The composition and content of reactants and products were analyzed by gas chromatography, and the data processing method was normalization. To ensure the test accuracy, the results were recorded after the specified temperature was reached and maintained for 25 minutes. Three groups of tests were performed, and the average value was the catalytic performance data at that temperature. The test results are shown in Table 1.
[0062] Table 1 Catalytic performance
[0063] sample Temperature / ℃ Acetylene conversion rate / % Ethylene selectivity / % Example 1 178 100 92 Example 2 160 80 94 Example 3 190 80 88 Example 4 200 85 90 Example 5 185 100 89
Claims
1. Application of a non-precious metal-based catalyst modified with a p-zone non-metallic element, characterized in that: It is used to catalyze the reaction of alkynes to olefins. The reaction temperature is 70-200°C, the molar ratio of hydrogen to alkynes in the reaction raw gas is 1 / 1-20 / 1, the test pressure is 1-4 bar, and the space velocity is 5000-240000h -1 The preparation method of the non-precious metal-based catalyst modified by the p-zone non-metallic element comprises the following specific steps: A. Dissolve the soluble transition metal salt and the organic ligand in excess N,N-dimethylformamide at a molar ratio of 1 to 2 / 1 to prepare a solution with a transition metal concentration of 70.0 to 110.0 mmol / L; transfer the solution to a reactor, crystallize at 120 to 150°C for 12 to 20 hours, cool naturally to room temperature, centrifuge, wash, and place in a constant temperature drying oven at 60 to 90°C for 12 to 24 hours to obtain a transition metal-based organic metal framework material M-MOF; The soluble transition metal salt is one or two of Ni(NO3)2·6H2O, NiCl2, Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Zn(NO3)2·6H2O, FeCl2·4H2O, wherein M is one or two of the corresponding transition metals Ni, Co, Cu, Fe, Zn; the organic ligand is one of terephthalic acid, 2,2-bipyridine or 2,5-dihydroxyterephthalic acid; B. dissolving a compound containing a p-region non-metal X in excess anhydrous methanol to prepare a solution with a concentration of 2 to 6 mol / L, and mixing it with the M-MOF prepared in step A at an X / M molar ratio of 1 / 5 to 1 / 15, stirring continuously at a constant temperature of 25 to 60° C. for 10 to 20 hours, centrifugally filtering and washing, and drying in a constant temperature drying oven at 60 to 90° C. for 12 to 24 hours to obtain a p-region non-metal X-modified transition metal-based organic metal framework material, denoted as MX-MOF; The compound containing the p-block non-metal X is one or two of dimethyl sulfoxide, thiourea, dicyandiamide, triphenylphosphine, sodium hypophosphite or boric acid; C. The MX-MOF obtained in step B is placed in a fixed bed reactor, and the temperature is raised to 200-600°C at a rate of 2-20°C / min in an inert atmosphere, and maintained for 1-3 hours to induce a structural topological transformation of the MOF. After cooling to room temperature, a highly dispersed M-MOF modified with non-metallic X in the p region is obtained. 2+ -X / C precursor; The inert atmosphere is one of N2, Ar or He; D. placing the sample obtained in step C in a micro fixed bed reactor, introducing a reducing atmosphere, heating the temperature to 200-600° C. at a heating rate of 2-20° C. / min, and maintaining the temperature for 1-3 hours for activation, and cooling the temperature to room temperature to obtain a carbon-supported non-precious metal-based catalyst modified with a p-region non-metallic element, expressed as vM-wX / C; M represents a transition metal, X represents a p-region non-metallic element, v represents the loading amount of the transition metal M, and w represents the loading amount of the p-region non-metallic element X; The reducing atmosphere is one of 5-40 vol.% H2 / N2 or 5-40 vol.% CO / N2.
2. The use of a non-precious metal-based catalyst modified with a p-zone non-metallic element according to claim 1, characterized in that: The compound containing p-block non-metal X in step B is one or two of dimethyl sulfoxide containing S atoms, sodium hypophosphite containing P atoms or boric acid containing B atoms; the molar ratio of the p-block non-metal element X to the transition metal M in step B is 1 / 5 to 1 / 10; and the temperature in step D is raised to 300 to 500° C.
3. The use of a p-zone non-metallic element modified non-noble metal-based catalyst according to claim 1, characterized in that: In vM-wX / C, M is a transition metal with hydrogenation activity, and M is one or two of Ni, Co, Cu, Fe, and Zn; X is one or two of the p-zone non-metallic elements P, S, N, and B; v represents the loading amount of the transition metal M, v=5.0%~20.0wt.%; w represents the loading amount of X, w=0.5~2.0wt.%.
4. The use of a p-zone non-metallic element modified non-noble metal-based catalyst according to claim 3, characterized in that: The M is one or both of Ni and Cu, and the p-zone non-metallic element is one or both of S, P and B.
Citation Information
Patent Citations
Nonmetallic bifunctional oxygen catalyst based on ZIF-8 and double-doped with phosphorus and sulfur, and preparation method and application thereof
CN109012749A
Synthesis method of S-doped metal organic framework material
CN109021248A